2021
DOI: 10.1080/21655979.2021.1954580
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin attenuates traumatic tracheal stenosis in rats and inhibits lung fibroblast proliferation and differentiation via TGF-β1/Smad and Akt/mTOR pathways

Abstract: Traumatic tracheal stenosis (TS) is a serious respiratory disease characterized by hyperplasia of airway granulation. Plumbagin (PLB) is a natural naphthoquinone component with anti-fibrotic properties. This research aimed to explore the roles of PLB in alleviating TS and the underlying mechanisms. For in vitro studies, lung fibroblasts (IMR-90 cells), with/without PLB treatment or TGF-β1 induction, were used. The viability and proliferation of IMR-90 cells were examined by CCK-8 and EdU incorporation assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
2
10
0
3
Order By: Relevance
“…Among them, inflammatory signaling pathways such as TNF, NF-κB, and toll-like receptor signaling pathways; fibrosis signaling pathways such as MAPK, JAK-STAT, Ras, Rap1, Notch, and Wnt signaling pathways; and PI3K-Akt, mTOR, HIF-1, and PPAR signaling pathways were found to be enriched. These results indicate the important role of inflammation and fibrosis in TTS development, which is consistent with the studies by Xiao et al (2020 ), Fan et al (2021 ), and SHI et al (2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Among them, inflammatory signaling pathways such as TNF, NF-κB, and toll-like receptor signaling pathways; fibrosis signaling pathways such as MAPK, JAK-STAT, Ras, Rap1, Notch, and Wnt signaling pathways; and PI3K-Akt, mTOR, HIF-1, and PPAR signaling pathways were found to be enriched. These results indicate the important role of inflammation and fibrosis in TTS development, which is consistent with the studies by Xiao et al (2020 ), Fan et al (2021 ), and SHI et al (2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…This research proved a strong correlation between the secretion of TGF‐β1 and the number of these two immune cell subtypes, indicating that immune cells may be crucial in the onset and progression of TS through aberrant secretion of TGF‐β1 and other cytokines. Previous reports on TS fibrosis have mainly focused on the TGF‐β1 pathway 46–48 . Therefore, this paper discussed the new possibility that the imbalance of immune cells and the secretion of cytokines may affect the occurrence and development of TS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on TS fibrosis have mainly focused on the TGF‐β1 pathway. 46 , 47 , 48 Therefore, this paper discussed the new possibility that the imbalance of immune cells and the secretion of cytokines may affect the occurrence and development of TS. At present, studies have constantly explored the potential of immune cells as targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…(Karagiannidis, et al 2006 ). Previous studies have suggested that the genesis and progression of BAS are caused by airway mucosal inflammation, mucosal abnormal hyperplasia, epithelial-mesenchymal transition (EMT) and fibrous scar formation under the influence of various factors, such as infection, trauma and hypoxia, which leads to stenosis (Shi, et al 2021 ; Wu, et al 2021 ; Wei, et al 2023 ). Owing to the action of cytokines like transforming growth factor-β1 (TGF-β1) following BAS, tracheobronchial fibroblasts aberrantly aggregate and proliferate, which results in the proliferation of granulation tissues and fibrosis (Wu, et al 2021 ; Xu, et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%